Perceptions, attitudes and practices regarding canine zoonotic helminthiases among dog owners in Nyagatare district, Rwanda - Pie Ntampaka; François Niragire; Vincent Nkurunziza; Gisele Uwizeyimana; Anselme Shyaka (Veterinary Medicine and Science, 2022)
Abstract Background Despite their importance to society, dogs are susceptible to various helminths. This study aimed to understand perceptions, attitudes and practices (PAP) regarding canine zoonotic helminthiases (CZH) among dog owners in Rwanda. Methods A cross‐sectional study was carried out in Nyagatare district of Rwanda, where 203 dog owners were randomly selected and interviewed. To analyse this study's data, we used frequency distributions, chi‐square test of association and binary logistic regression model. Results Overall, 75.9% and 30% of the respondents were aware of canine and human helminthiases, respectively. Around 74.4% knew that dogs source helminthiases from eating raw infected meat. Also, 74.4% knew vomiting, diarrhoea and swelling of the belly as clinical signs of the helminthiases. Around 58.6% washed hands with soap and water after handling a dog. Only 17.2% and 15.5% dewormed the dogs and treated them against ectoparasites using conventional anthelmintics and acaricides manufactured for dogs, respectively. Of all respondents, 33% held genuine perceptions, while 78.3% and 25.1% adopted positive attitudes and appropriate practices about CZH, respectively. The respondents’ educational level and length of dog ownership correlated with their perceptions and practices about CZH, respectively, while sources of information on CZH influenced their PAP of such infections. The adjusted odds ratio (OR) of having genuine perceptions and positive attitudes were more than 82% lower among those who sourced the information from neighbours & colleagues compared to those who gathered it through reading. Again, the length of dog ownership (OR = 0.37, 95% CI: 0.15–0.90) correlated with the respondent's practices about CZH. Conclusions Only 33% and 25.1% of the respondents held genuine perceptions and adopted positive attitudes regarding CZH, respectively. The findings indicate increased zoonotic helminths in dogs, possible spillover in humans and anthelmintic resistance. Therefore, awareness campaigns are needed to upgrade dog owners’ knowledge of the zoonotic helminthiases in dogs in Nyagatare district.